Α‐Synuclein RT‐QuIC assay in cerebrospinal fluid of patients with dementia with Lewy bodies. Issue 10 (10th October 2019) - Bongianni, Matilde; Ladogana, Anna; Capaldi, Stefano; Klotz, Sigrid; Baiardi, Simone; Cagnin, Annachiara; Perra, Daniela; Fiorini, Michele; Poleggi, Anna; Legname, Giuseppe; Cattaruzza, Tatiana; Janes, Francesco; et al.
Abstract: We applied RT‐QuIC assay to detect α‐synuclein aggregates in cerebrospinal fluid (CSF) of patients with suspected Creutzfeldt–Jakob disease who had a neuropathological diagnosis of dementia with Lewy bodies (DLB) ( n = 7), other neurodegenerative diseases with α‐synuclein mixed pathology ( n = 20), or without Lewy‐related pathology ( n = 49). The test had a sensitivity of 92.9% and specificity of 95.9% in distinguishing α‐synucleinopathies from non‐α‐synucleinopathies. When performed in the CSF of patients with DLB ( n = 36), RT‐QuIC was positive in 17/20 with probable DLB, 0/6 with possible DLB, and 0/10 with Alzheimer disease. These results indicate that RT‐QuIC for α‐synuclein is an accurate test for DLB diagnosis.